IDENTITAS KE-AMBON-AN DALAM KUASA ADAT - Batlayeri, Willem (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2017)
This article is a reflection which is meant to be a critical opinion on adat (local customs and tradition) issues in Ambon, specifically since 1998, when many people indulged in talking about adat. Adat should not be looked upon as managing certain objects and valuables, reducing them to traditional appreciation. Nowadays it is important to deliberate in which way adat is being deliberated. In this context Michel Foucault’s analysis on power will be used as the main device of analysis. With the help of Foucault, we will try and scrutinize in wider scope, how to distance ourselves from being trapped in any power which is used in the name of adat.